2009
DOI: 10.1007/s00439-008-0616-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the MTHFD1 promoter and risk of neural tube defects

Abstract: Genetic variants in MTHFD1 (5,10-methylenetetrahydrofolate dehydrogenase/ 5,10-methenyltetrahydrofolate cyclohydrolase/ 10-formyltetrahydrofolate synthetase), an important folate metabolic enzyme, are associated with a number of common diseases, including neural tube defects (NTDs). This study investigates the promoter of the human MTHFD1 gene in a bid to understand how this gene is controlled and regulated. Following a combination of in silico and molecular approaches, we report that MTHFD1 expression is cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
15

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 32 publications
3
27
0
15
Order By: Relevance
“…Furthermore, MTHFD1 SNP 1958GN A is a functional exonic SNP that has been studied in several populations, and the previous studies that indicate the genetic variants of MTHFD1 can result in some kind of diseases [3,[23][24][25][26][27][28][29][30]. In Carroll N's analysis, he revealed that MTHFD1 SNP 1958G N A (R653Q) has a highly significant association with NTD risk in both case (genotype and allele frequencies) and maternal (allele frequencies only) groups [16]. And in the study of Ridgely F.G., the cause of NTD was considered to be consistent with both genetic and epigenetic mechanisms contributing to the increased risk of NTD and overall birth defect risk in the maternal lineage which had a higher number of genotypes associated with lower folate metabolism than paternal relatives [31].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, MTHFD1 SNP 1958GN A is a functional exonic SNP that has been studied in several populations, and the previous studies that indicate the genetic variants of MTHFD1 can result in some kind of diseases [3,[23][24][25][26][27][28][29][30]. In Carroll N's analysis, he revealed that MTHFD1 SNP 1958G N A (R653Q) has a highly significant association with NTD risk in both case (genotype and allele frequencies) and maternal (allele frequencies only) groups [16]. And in the study of Ridgely F.G., the cause of NTD was considered to be consistent with both genetic and epigenetic mechanisms contributing to the increased risk of NTD and overall birth defect risk in the maternal lineage which had a higher number of genotypes associated with lower folate metabolism than paternal relatives [31].…”
Section: Discussionmentioning
confidence: 96%
“…In our meta-analysis, we extracted data from 9 relevant articles [1,[8][9][10][15][16][17][18][19]; they were all selected through a pre-specified search strategy. Quality assessment for the overall studies was shown with a bar graph according to the Newcastle-Ottawa Scale tool in Fig.…”
Section: Meta-analysis Of the Association Between 1958gn A And Ntd Riskmentioning
confidence: 99%
“…Finally, knockout of MTHFD1, a gene required for purine biosynthesis, resulted in abnormal neural tube closure and premature death around embryonic day 10.5 (e10.5) [28]. In human, SNPs existing within the promoter region of MTHFD1, have been associated with increased NTD risk [29].…”
Section: Brief Timelinementioning
confidence: 99%
“…On the contrary, the T-allele of rs1076991 polymorphism has been suggested to decrease the MTHFD1 promoter activity by nearly 70%, 11 which may reduce the MTHFD1 flux. Meanwhile, increased intracellular glycine was associated with impaired 5,10-methylenetetrahydrofolate, possibly because of reverse flux through serine hydroxymethyltransferase.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…The minor A allele of rs2236225 has been shown to decrease de novo purine synthesis rate, 10 while the minor T allele of rs1076991 has been associated with nearly 70% decrease of MTHFD1 promoter activity. 11 We, therefore, assessed whether associations of plasma serine and glycine with risk of AMI were influenced by the MTHFD1 polymorphisms among SAP patients included in the WENBIT (Western Norway B Vitamin Intervention Trial).…”
Section: Circ Cardiovasc Genet December 2016mentioning
confidence: 99%